Les doubles modaux anglais, témoins d’un changement de catégorie - Patrice Larroque (Anglophonia)
Current English varieties have a class of modal verbs which are syntactically and morphologically irregular. In Standard English these verbs do not have a third person -s present tense inflection, an -ing form, a past participle; they do not permit a direct object and are not followed by another modal verb.While a double modal construction was possible in Early Modern English and is still found in some regional non-standard varieties in the southern states of America, the north of England (in the Midlands), and Scotland, it is no longer in use in Standard English.Although such structures as I might could be able to visit ..., I’d might just let you know, She shouldn’t ought to be there, We’ll shall go, erm, go to the market, are now accounted mistakes, they are nonetheless diachronically and synchronically interesting. Historically, English has, between the 16th and the 19th century, undergone a category change and innovated a new class of verbs. From a synchronic point of view, double modal constructions may bring out, among other things, the root and the epistemic readings of a modal.The study, therefore, confronts the modal system in the English grammar, past and present, with current double modal constructions in an attempt to account for the grammaticalness of the latter.